Thermodynamic simulation of biogas composition in agricultural waste gasification - Muhammad Syafiq, Aziz (2013)
Being one of the world¡¯s largest producers of palm oil, Malaysia has an abundant supply of oil-palm fronds due to the large plantation areas in the country. Considering the large and consistent supply, oil-palm fronds could be a promising source of biomass energy through gasification. In this work, the study is conducted by thermodynamic simulation to determine the biogas composition of oil palm fronds (OPF). Computer simulation using MATLAB is performed to predict composition of the synthesis gas. A preliminary gasification of oil palm fronds is conducted to understand the process and to improve the study in the future. It is proven that oil palm fronds are feasible for gasification and have a good potential as a renewable energy source. Biomass gasification is a thermochemical process of converting biomass into the producer gas or synthesis gas which can be subsequently used for heat, power and liquid fuels production through various synthesis processes. The major objective of this study was to identify the biogas composition from oil palm fronds (OPF) by thermodynamic simulation using thermodynamic equilibrium model as suit to the Gibbs equations and formulations. Few assumptions were made as to ease the analysis of data. Results obtained were tabulated and graphs were sketched. Different temperature with range of 650¢ªC to 1200¢ªC is the manipulate variable. The composition of combustible gases was decreasing as the temperature increase. Also as the moisture content is increase, the composition of CO decrease, while other gases were slightly increases and decreases.